Computed tomography of primitive neuroectodermal tumors. - Ganti, S R; Silver, A J; Diefenbach, P; Hilal, S K; Mawad, M E; Sane, P (American Journal of Neuroradiology, 1983)
The primitive neuroectodermal tumor is a neoplasm of young individuals that occurs predominantly in the supratentorial compartment. It appears on computed tomography as a bulky mass, often with calcification with predominantly homogeneous enhancement but on occasion with cystic or necrotic areas. Cerebrospinal fluid seeding was observed in more than half the cases in our series. The patients had a short survival period (7-24 months). Despite surgery, radiation, and chemotherapy, further growth of this tumor has not been prevented.